Habits of Using Private Gardens and Green Spaces in Suburban Villages around Nitra - Hardi, Tamás; Repaská, Gabriela; Páthy, Ádám; Veselovský, Ján (Geographica Pannonica, 2025)
The growth of suburbs alters the traditional villagescape due to increasing population and new housing developments. This not only affects the buildings but also alters the green spaces within the settlements. The amount of green space is decreasing as more densely populated developments are built. Additionally, most green spaces in villages are privately owned, with gardens making up the majority of these areas. Our study examines the attitudes of the population towards gardening and greening in four settlements near Nitra, Slovakia. Through questionnaires we explore how the attitudes of both newcomers and local residents differ and how this varies between the different settlements, to identify any differences in attitudes towards gardening.